2017
DOI: 10.1556/2051.2017.00055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si3N4 addition on the morphological and structural properties of the 316L stainless steel for nuclear applications

Abstract: The effect of the submicrometer-sized Si 3 N 4 addition on the morphological and structural properties of the ceramic dispersion strengthened (CDS) 316L stainless steels prepared by powder technology has been studied. Two composites were prepared: 316L/0.33 wt. % Si 3 N 4 and 316L/1 wt. % Si 3 N 4 . In order to assure a good dispersion of the ceramic particles in the stainless steel powders and a grain size reduction at the same time, the high efficient attrition milling has been used. Spark plasma sintering (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…A comparison of the XRD diffraction patterns of the starting powders and the milled powders (Figure 6) confirmed that the powders had a crystalline structure of an FCC γ-Fe The formation of a small fraction of the α phase was related to a partial phase transformation induced by the severe plastic deformation during the milling process. The formation of a similar α phase after milling was observed in our previous work on Si 3 N 4 [16] and SiC [15] dispersion-strengthened 316L steel. Al-Joubori et al observed the formation of a similar α phase [38].…”
Section: Morphological and Structural Investigationsupporting
confidence: 80%
See 3 more Smart Citations
“…A comparison of the XRD diffraction patterns of the starting powders and the milled powders (Figure 6) confirmed that the powders had a crystalline structure of an FCC γ-Fe The formation of a small fraction of the α phase was related to a partial phase transformation induced by the severe plastic deformation during the milling process. The formation of a similar α phase after milling was observed in our previous work on Si 3 N 4 [16] and SiC [15] dispersion-strengthened 316L steel. Al-Joubori et al observed the formation of a similar α phase [38].…”
Section: Morphological and Structural Investigationsupporting
confidence: 80%
“…This increase in the microhardness values was related to the addition of the harder nanosized alumina particles and to the presence of hardened particles as a result of the severe plastic deformation during the attrition milling process. Both the 316L/Al 2 O 3 composites showed lower microhardness results compared with the other composites prepared by the same process [15,16,42,43] (Figure 9).…”
Section: Investigation Of the Density And Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The 316L/Y 2 O 3 composites are harder than the 316L reference sample as it is represented in Fig 12. The HV values: 1.75±0.05, 2.63 ± 0.32 and 2.33 ± 0.165 GPa have been measured for the 316L (reference), 316L/0.33wt% Y 2 O 3 and the 316L/1 wt% Y 2 O 3 respectively. The 316L/ 0.33wt% Y 2 O 3 composite was showing somewhat higher hardness values than the 316L/1 wt% Si 3 N 4 composite from our previous work [20]. The friction coefficient dropped with addition of Y 2 O 3 .…”
Section: Morphological and Structural Investigationmentioning
confidence: 52%